Makna Filosofi Pembuatan Kaddo Bulo di Kecamatan Barombong Kabupaten Gowa - Fikram Nurzaman Kahar; St. Junaeda (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
The Philosophical Meaning of Making Kaddo Bulo in Barombong Sub-District Gowa District aims to discuss the process of making Kaddo Bulo which is held annually at a time that is usually not far from the anniversary of Indonesia’s independence on August 17th. Usually right after the rice harvest. There are philosophical meanings and values contained in the process of the birth of Kaddo Bulo in the East Tamala’lang community. Judging from the research objectives included in this Descriptive Research, using the Observation and Interview methods to several people who understand the history, process and content of the philosophical meaning in it. The results of this study indicate that there are philosophical values, both material, vital, historical, spiritual, and social or mutual cooperation which are the impetus or motivation for them to carry out traditions that have been preserved for hundreds of years.